The Covid-19 Pandemic and the Patterns of Nature - Gregory, Warr; Les, Hatton (International Journal of Coronaviruses, 2024)
This paper addresses broadly the impact that unprecedented levels of scientific discovery can have on the emergent global patterns that we observe in nature. An essentially ubiquitous pattern that is associated with large complex discrete systems is attributable to the Conservation of Hartley-Shannon Information (CoHSI). One of the manifestations of CoHSI in the realm of protein structure is a distinctive equilibrium distribution of protein lengths that is dominated by a power-law. Here we examine the manner in which the accelerated pace of novel protein discovery during the Covid-19 pandemic affected this distribution, showing that despite an initial disruption, nevertheless the equilibrium state was reestablished.
Keywords: SARS-CoV-2; Conservation Principle; Statistical Mechanics; Hartley Shannon Information; Power-Law; Protein Length